The efficacy of glycolic acid, salicylic acid, gluconolactone, and licochalcone A combined with 0.1% adapalene vs adapalene monotherapy in mild-to-moderate acne vulgaris: a double-blinded within-person comparative study - Kantikosum K; Chongpison Y; Chottawornsak N; Asawanonda P (Dove Medical Press, 2019)
Kornphaka Kantikosum,1 Yuda Chongpison,2 Natcha Chottawornsak,1 Pravit Asawanonda1 1Division of Dermatology, Department of Medicine, Faculty of Medicine, Chulalongkorn University, Bangkok, Thailand; 2Center of Excellence in Biostatistics, Research Affairs, Faculty of Medicine, Chulalongkorn University, Bangkok, Thailand Background: Acne vulgaris is a common and chronic disease that impacts on physical and psychological perceptions. Cosmeceutical products are widely used as adjunct therapy to standard treatments. Objective: To evaluate the efficacy of cosmeceutical products comprising glycolic acid, salicylic acid, gluconolactone, and licochalcone A as adjunct therapy to adapalene in mild-to-moderate acne vulgaris. Materials and methods: A 28-day, double-blind, within-person comparative study was conducted with a total of 25 subjects. Each participant received two products, consisting of (1) a cosmeceutical product mixed with 0.1% adapalene, and (2) 0.1% adapalene, and was asked to apply them separately on each hemi-side once nightly for 28 days. The number of acne lesions, severity of acne vulgaris, physician’s and patient’s global assessment of acne severity, visual analog scale of radiance, skin biophysics, safety assessment, and VISIA® camera system were evaluated. The primary efficacy outcome was to compare the reduction of inflammatory lesions between two treatments at day 7 by using non-inferiority comparison. Results: The mean differences of inflammatory lesions reduction at day 7 between the two groups was 0.391 (90% CI = 0.253–0.530). The differences between two groups fell within our acceptable margin for the 90% CI. The spot score from VISIA® showed higher statistically significant improvement in the combination side. Conclusion: The results showed no hindrance of using a cosmeceutical combined with standard treatment. Nevertheless, this cosmeceutical product showed some benefits in reducing complications from acne. Clinical trial registration: Thai Clinical Trials Registry (primary site), no. TCTR20171031005. Keywords: acne vulgaris, cosmeceutical, moisturizer, adapalene, retinoids